THE IMPORTANCE OF GOLD IN ENSURING ECONOMIC STABILITY - Kadirov Ermat Toshpulatovich (American Journals, 2025)
This article analyzes the formation process of the gold market, its current state, and future development prospects. The main objective of the study is to identify key trends emerging in the course of the comprehensive reform of the national gold market, examine existing challenges through a systematic approach, and develop scientifically grounded proposals and recommendations to address them.
Keywords: Gold market, price stability, investment potential, regulatory policy, gold reserves.